China’s Aid policy approach to Poverty Alleviation in the recipient country: A Case study of the Republic of Guinea - Ansoumane Douty Diakite (Journal of Social Studies (JSS), 2023)
This paper examines the extent to which China’s aid policies integrate poverty alleviation as a goal of their aid in general, particularly in Guinea. More specifically, the paper analyzed how aid donors focus on poverty alleviation and which policies and mechanisms are in place to address poverty in the countries receiving aid. Regarding the methodology, the author collected data from secondary sources, including government declarations of donors, policy documents at both the donor and recipient levels, as well as from scholarly publications. The following findings resulted from study:  China’s aid policies have progressively incorporated poverty alleviationobjectives and identified sectors for intervention against poverty. However, the limitations of China approach to poverty is that China adopts a top-down approach to poverty reduction and lacks of an impact evaluation mechanism based on poverty alleviation.